Sustainable Forest Management from the Perspective of Customary Law in Indonesia: A Case Study in the Bayan Community - Harly, Lalu Noval Banu (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The Indonesian government has not been able to realize sustainable forest management under the 1945 constitutional mandate, causing much forest damage. Indonesia urgently needs good forest governance. Therefore, it is essential to give a more significant role to local communities in managing forests in the future. The primary objective of this research project is to find sustainable forest management practices based on the customary law of the Bayan community. This research uses the literature review and case study method. An additional objective of this research is to study the problems that occur due to the absence of legal protection for local communities with regard to forest use and conflicts. This research demonstrates that the Indonesian government provides extensive support to the private forestry sector (for example through award of permits) and has ignored the rights of people who live around the forest. Forest management through customary law, such as Awiq-awiq in Bayan village, can provide great economic, social, and cultural benefits to local communities. Awiq-awiq regulates prohibitions, sanctions, and the procession of the customary assembly in association with forest management, and has been an effective way to use forests sustainably. The local community is highly compliant with awiq-awiq because they have been directly involved in drafting and reviewing this regulation. The customary law approach used by the Bayan community is an example of sustainable forest management practices that run well; and could be a valuable model for the Indonesian state and other forest conservation managers to consider.